Facilitation of Pre-schooler’s Purposefulness in Art Activities - Priede, Ligita; Vigule, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Creative, responsible, independent personality, which is showing respect and tolerant to others is a value not only in education but also in democratic society. Will is one of the most important characteristics of personality. Development of child’s will in pre-school age is based not only to its direct formation, but it is more like issue of child’s general development. Art activities facilitate development of will qualities in case, if child’s activity is motivated and caused by positive emotions. Motivation is one of the most relevant conditions in will development – setting up purpose, decision making, and successful achievement of purpose emerge from that. They provide in art activities child’s natural desire to act and also learning of definite knowledge and skills are facilitated. They develop child’s independence, performance and purposefulness. The aim of study – to turn attention to theoretical and empirical aspects which are important in facilitation of pre-schooler’s purposefulness in art activities.